Pengaruh Penambahan Carboxymethyl Cellulose Terhadap Sifat Fisik, Mekanik dan Biodegradasi Plastik Biodegradable Berbasis Selulosa Bakteri –Sorbitol dari Air Kelapa (Cocos nucifera) - Sukardi, Azaria Saiza; Putra, Ananda (Departemen Kimia FMIPA UNP, 2024)
Biodegradable plastic is one solution to overcome environmental problems because it is easily degraded by microorganisms. This study was conducted to determine the effect of adding additives in the form of Carboxymethyl Celluose (CMC) on biodegradable plastic based on bacterial cellulose from coconut water (Cocos nucifera) with sorbitol as a plasticizer. The addition of additives in the form of Carboxymethyl Celluose (CMC) with mass variations of 0 gr, 1 gr, 3 gr, 5 gr, and 7 gr to improve the quality of biodegradable plastics in order to replace conventional plastics and determine the physical, mechanical and biodegradation properties. The results of the physical properties test obtained are the value of % water content and the degree of inflatation in plastic increases with the addition of CMC mass. The best results from mechanical properties testing obtained were the addition of CMC 5 gr with tensile strength values of 101 MPa, elasticity of 466.11 MPa, and elongation of 21.71%. In biodegradation testing, plastics with the best mechanical properties have been completely degraded for 12 days.